Bulk Superlattice Analogues for Energy Conversion - Bai, Wei; Xiao, Chong; Xie, Yi (Journal of the American Chemical Society, 2022)
Energy storage and conversion in a clean, efficient, and safe way is the core appeal of a modern sustainable society, which is built on the development of multifunctional materials. Superlattice structures can integrate the advantage of their sublayers while new phenomena may arise from the interface, which play key roles in modern semiconductor technology; however, additional concerns such as stability and yield challenge their large-scale applications in industrial products. In this Perspective we focus our interest on a distinctive category of easily available multilayered inorganic materials that have well-defined subunit structures and can be regarded as bulk superlattice analogues. We illustrate several specific combining forms of subunits in bulk superlattice analogues, including soft/rigid sublayers, electron/phonon transport sublayers, quasi-two-dimensional layers, and intercalated metal layers. We hope to provide insights into material design and broaden the application scope in the field of energy conversion by integrating the versatility of subunits into these bulk superlattice analogues.